Losses in Translating Arabic (Quranic) Marked Structures into English - Al-kuran, Mohammad Ahmad (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
Although foregrounding is an Arabic basic feature that is recurrent in the Quran, English available translations of the Quran have failed to observe the syntactic order of the source text due to the linguistic limits of English. This paper attempts to highlight the semantic loss in translating Quranic marked order into English in both affirmative and negative structures. It also highlights the appropriate linguistic techniques translators can use to make up for syntactic difference between the two languages. The study is based on Arabic theory of grammar at the core of which foregrounding plays a central role in communicating the message. The findings show it is possible to overcome word order rigidity by making appropriate linguistic alterations. The study concludes that the translator’s unawareness of the ST marked constructions is likely to lead to a semantic loss in the translations, because of the syntactic differences between the ST and TT.